Implementasi Learning Management System (LMS) Melalui Website dan E-Learning untuk Meningkatkan Keterampilan Pendidik - Warsono, Miswadi (Jurnal Didaktika Pendidikan Dasar, 2021)
The problem of this research is "How the implementation of the Learning Management System (LMS) through the Website and E-Learning to improve the teachers skill in Distance Learning (PJJ) at Sekolah Menengah Pertama Negeri 4 Bobotsari in the first semester of the 2020/2021 academic year?". The subjects of this research were all the teachers of Sekolah Menengah Pertama Negeri 4 Bobotsari totaling 18 people consist of 5 boys and 13 girls.  Type of the research used is the School Action Research (PTS) with a qualitative approach. The research data got from the teacher's skill data in two cycles. Teacher skill data were collected from direct observation in e-learning in each cycle. The percentage results of teachers' skill on the first cycle were 62% and the second cycle was 71%. There was an increase of 9% of teachers skill.